2007
DOI: 10.1097/mlr.0b013e3180ca960e
|View full text |Cite
|
Sign up to set email alerts
|

Is Lower 30-Day Mortality Posthospital Admission Among Blacks Unique to the Veterans Affairs Health Care System?

Abstract: These findings suggest that factors associated with better short-term outcomes for blacks are not unique to the VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Our findings support previous research from administrative data and stroke registries, suggesting that racial/ethnic minority groups have a lower risk for short-term all-cause mortality after being hospitalized for AIS than non-Hispanic white patients. 9,[29][30][31][32] One possible explanation for such findings is that there are relatively high rates for small vessel lacunar and intracranial atherosclerotic stroke types compared with large-vessel cardioembolic stroke type among racial/ethnic minority patients compared with non-Hispanic whites. 4,[33][34][35][36] Another possible explanation is that racial/ethnic minority patients might receive intensive life-sustaining interventions more often, which could lead to a short-term survival advantage.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings support previous research from administrative data and stroke registries, suggesting that racial/ethnic minority groups have a lower risk for short-term all-cause mortality after being hospitalized for AIS than non-Hispanic white patients. 9,[29][30][31][32] One possible explanation for such findings is that there are relatively high rates for small vessel lacunar and intracranial atherosclerotic stroke types compared with large-vessel cardioembolic stroke type among racial/ethnic minority patients compared with non-Hispanic whites. 4,[33][34][35][36] Another possible explanation is that racial/ethnic minority patients might receive intensive life-sustaining interventions more often, which could lead to a short-term survival advantage.…”
Section: Discussionmentioning
confidence: 94%
“…A "reverse disparity" in the race-mortality relationship, where NHB elderly (>65 years old) have a survival benefit over elderly NHW, has been demonstrated in studies examining allcause or specific cause-related deaths in individuals with diabetes [8][9][10][21][22][23] . The sample in this study represents an older (generally elderly) cohort of individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…While there is an established evidence base for differences in mortality among blacks and whites, racial disparities in mortality among a high-risk population of veterans with diabetes lacks strong convincing data. The results of several large-scale studies have used administrative data to support the finding of lower mortality among elderly black veterans 8 ; not among those younger than 65 years of age 9,10 . A major limitation of administrative datasets in reporting disease states is its heavy dependence on accurate coding for record-keeping and/or payment purposes 11 rather than accurate patient-level data, thus providing a picture for disease burden but lacking in other important confounders.…”
Section: Introductionmentioning
confidence: 90%
“…The single study that addressed timeliness of care showed worse performance among veterans in VA facilities relative to non-VA facilities for time between hospital admission for hip fracture and surgical repair. 37 Four studies examined equity, with one study showing better performance on several chronic disease and preventive measures, 51 one study showing worse performance in VA facilities for emergency room visits among cancer patients in the last month of life, 76 and two studies showing similar equity in 30-day post-admission mortality 78 and graft failure. 27 Nine articles compared efficiency using utilization, with six studies showing worse performance in VA facilities on outcomes such as average length of stay and service utilization for patients on dialysis, 32,61,[79][80][81][82] two showing better performance for visits/ admissions 83 and generic drug utilization, 84 and one with mixed results for utilization-related inpatient quality indicators.…”
Section: Safetymentioning
confidence: 99%